IoT Innovation and Entrepreneurship Education: Sustainable Tilapia Cultivation Optimization Strategy - Samsumar, Lalu Delsi; Kembang, Lale Puspita; Akbar, Ardiyallah; Sriasih, Sriasih; Zaenudin, Zaenudin; Kalbuadi, Amiruddin (Pascasarjana Universitas Mataram, 2024)
Tilapia cultivation in Teratak Village, Central Lombok, faces problems in feed efficiency and limited market access. Lack of automation technology causes feed waste, while limited marketing knowledge limits farmers' competitiveness. This community service activity aims to overcome these problems through the application of Internet of Things (IoT) technology in the form of automatic feeders (smart feeders) and entrepreneurship training focused on digital marketing. The methods applied include the manufacture and installation of smart fish feeders that are controlled via an application to regulate the amount and frequency of feed. In addition, entrepreneurship training focuses on digital marketing strategies through social media and e-commerce platforms to expand market reach. The results of the activity show that smart feeders increase feed efficiency by up to 20%, reduce waste, and support more optimal fish growth. Digital marketing training helps farmers improve their online promotion skills, expand market networks, and significantly increase sales. In conclusion, the application of IoT technology and digital marketing-based entrepreneurship training has proven effective in increasing the efficiency of cultivation and market competitiveness of tilapia farmers in Teratak Village